Analisis Pengaruh Kompensasi dan Beban Kerja Terhadap Turnover Intention - Dwi Murti, Anisa; Sheviyani, Hafivah; Sekar Desiree, Hany; Setiawan, Ahmad (Rifa'Institute, 2023)
This study was conducted because turnover intention remains a common problem faced by companies, especially in the Cikarang area, Bekasi Regency. Compensation and workload are considered as factors that affect turnover intention. Therefore, this study aims to analyze the influence of compensation and workload on turnover intention as well as the influence of satisfaction on turnover intention in one of the companies in the area. Good human resource management is very important in creating employee welfare and achieving company goals. The analysis method used is quantitative method using survey type and data collection through questionnaires. This study used a sample of 32 people for the research sample. Therefore, the results of this study can contribute to the development of human resource management in companies, especially in addressing the problem of turnover intention.